EFEKTIFITAS KONSELING TERHADAP PENGETAHUAN IBU DALAM DETEKSI TANDA BAHAYA BAYI DAN BALITA DI INDONESIA - Anissa Rizkianti; Ika Saptarini; Suparmi Suparmi; Iram Barida Maisya; Andi Susilowati; Bunga Christita Rosha (JURNAL KESEHATAN REPRODUKSI, 2023)
Background: As part of the Integrated Management of Childhood Illnesses, the government conducted counselling on a daily monitoring, so families enable to recognize danger signs and seek medical help for sick infants and under-five children. Objective: This study aims to measure changes in mothers' knowledge about danger signs on infants and under-five children after given counseling regarding monitoring. Method: The study design used was a quasi-experiment in one group (one-group pretest-posttest) with a quantitative and qualitative approach. The quantitative sample was 320 under-five children in the selected public health centers in eight focused districts who met the inclusion criteria, consisting of mothers, caregivers, or the closest family members taking care of children, whereas the qualitative sample included four informants with classification based on monitoring practices. Counseling was conducted by local cadres who were formerly trained by the Ministry of Health team. Results: Of the 320 respondents, only 48.4% experienced better knowledge after receiving counseling. Based on the McNemar test results, respondents' knowledge level before and after counseling was not significantly different (p > 0.05). Qualitative results show that inappropriate counseling techniques and a less conducive environment affected changes in respondents' knowledge. Conclusion: To optimize the effectiveness of counseling in increasing mothers' knowledge to monitor danger signs for infants and under-five children at home, cadres are expected to design better counseling practices and create a conducive atmosphere. Keywords: counseling, monitoring, danger signs, knowledge